Deliberative democracy: public opinion and political will - Cuchumbé Holguín, Nelson Jair (Estudios de Filosofía, 2010)
The purpose of this paper is to reflect on the Political relationship and Legitimacy of the State in modern liberal societies, taking its bearings on the ideological confrontation between the promoters of the “State of Mind” and the defenders of the State of Law in Colombia. I believe that Participation, Deliberative Communication, Public Use of Practical Reason, Citizen Autonomy and the respect for Citizen’s Fundamental Rights are unavoidable ethical and political assumptions if we want to build a Democratic and Pluralistic Political Culture in Colombia. To justify my point of view, I´ll proceed as follows: Firstly, I´ll introduce the idea that Deliberative Democracy privileges the conflux of Political Pluralism in its full respect of both the law and the institutionalized procedures of communication between citizens and public institutions. Secondly, I will argue that Deliberative Democracy implies a democratic process subject to general impartial principles of Justice.